2022
DOI: 10.1590/2317-6431-2021-2597
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre o desempenho linguístico-cognitivo e a autopercepção auditiva de idosos

Abstract: RESUMO Objetivo analisar os desempenhos linguístico e cognitivo, a presença de relato de mudança na audição, a queixa e a autopercepção auditiva de idosos frequentadores de um centro comunitário brasileiro e verificar a associação entre essas variáveis. Métodos foram analisados os dados demográficos de 61 indivíduos; a presença de relato de mudança na audição nos últimos cinco anos e de queixa auditiva; o desempenho linguístico, por meio da Bateria Montreal-Toulouse; os resultados do teste de rastreio cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
(32 reference statements)
2
3
0
4
Order By: Relevance
“…In line with the results of the studies by Cruz, Pereira and Raymundo (2022), Cruz, Pereira, Pizzetti et al (2022), Fiamoncini et al (2022), Souza Júnior, Siqueira et al (2022, Balaguera and Arberas (2022), it was noticed that biopsychosocial educational activities positively interfere in psychological aspects, reflecting in the improvement of the quality of life of this portion of the population.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…In line with the results of the studies by Cruz, Pereira and Raymundo (2022), Cruz, Pereira, Pizzetti et al (2022), Fiamoncini et al (2022), Souza Júnior, Siqueira et al (2022, Balaguera and Arberas (2022), it was noticed that biopsychosocial educational activities positively interfere in psychological aspects, reflecting in the improvement of the quality of life of this portion of the population.…”
Section: Resultssupporting
confidence: 71%
“…In another study, Fiamoncini et al (2022) stated that the elderly had a high prevalence of hearing changes in the last five years and auditory complaints related to aging, associated with linguistic-cognitive performance, evidencing the relevance of longitudinal monitoring, communicative and cognitive performance of the elderly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present research found 68% of older people with a score suggestive of cognitive changes, while the cited studies identified respectively 55% and 16% of older people with this same clinical condition. On the other hand, a study with older people from the same region as this study also identified a high prevalence of older people (80%) with a clinical condition suggestive of cognitive changes, likewise through the MMSE (32) . Thus, it is believed that sociodemographic characteristics can justify cognitive results.…”
Section: Discussionsupporting
confidence: 50%
“…A presente pesquisa destaca 68% de idosos com escore sugestivo de alteração cognitiva, enquanto os outros estudos citados anteriormente identificaram, respectivamente, 55% e 16% de idosos com este mesmo quadro clínico. Por outro lado, um estudo desenvolvido com idosos da mesma região estudada também identificou alta prevalência de idosos, 80%, com quadro clínico sugestivo de alteração cognitiva, também por meio da aplicação do MEEM (32) . Assim, acredita-se que as características sociodemográficas podem justificar o resultado cognitivo, mas também é necessário referir que os dados normativos do instrumento foram obtidos com amostra de outra região do país, o que pode destacar ainda mais a relevância das variáveis demográficas na análise do quadro clínico cognitivo.…”
Section: Discussionunclassified